Pengembangan Marketing Capability Wisata Bahari Puger Berbasis Sustainability - Wulandari, Gusti Ayu; Nugraha, Kristian Suhartadi Widi; Paramita, Cempaka; Suryaningsih, Ika Barokah; Sari, Tria Putri Novia; Cahyani, Devina Widya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Puger Kulon is one of the areas on the coast of Jember City with qualified tourism potential and proven human resource commitment. However, it still needs more capabilities to develop and realize Puger as a Minapolitan Marine Tourism Destination in Jember and East Java. Puger Kulon managers and communities must avoid facing dynamic changes comprehensively and utilize modern digital marketing media to capture marketing opportunities as an attractive tourist destination. Branding efforts to increase tourist attractiveness can be observed from a comprehensive approach. This service activity aims to improve the ability of the Puger Maritime Tourism manager as a tourist destination with a focus on strengthening branding through a participatory rural appraisal approach to the community to be able to compile tour packages, profile videos, and training related to tourism development such as Hospitality and Tour Package Preparation so that Puger becomes a more marketable and attractive destination for tourists.